Analisis Determinan Kesempatan Kerja dan Kemiskinan pada Kabupaten/Kota di Sumatera Barat - Ahmaddizon Ahmaddizon; Hasdi Aimon (Universitas Negeri Padang, 2020)
This research focuses on analyzing and knowing the effect of job opportunities and poverty on Regencies/Cities in West Sumatra. This research is descriptive and inductive. The data used in this study is secondary data with data collection using panel data obtained from BPS West Sumatra Province 2013-2019 period with 19 districts / cities in West Sumatra. This study analyzed using a simultaneous equation model (simultaneous equation regression model). The results of this study conclude that (1) Government investment has an insignificant and positive impact on employment opportunities, private investment has a significant and positive impact on opportunities, economic growth has no significant effect and has a negative impact on employment opportunities. (2) Private investment has an insignificant and positive impact on poverty, economic growth has a significant and positive impact on poverty, education has a significant and negative impact, while job opportunities have an insignificant and negative impact on poverty in Regencies/Cities in West Sumatra 2013-2019.